Construction of rice husk-derived SiOx nanoparticles encapsulated with graphene aerogel hybrid for high-performance lithium ion batteries. (1st August 2022) - Sun, Mengfei; Xu, Zhengzheng; Liu, Kun; Yang, Hongxun; Yang, Tongyi; Jin, Chao; Wang, Zi; Jin, Yanchun; Chen, Lizhuang
Highlights: A rice husk-based SiOx /graphene aerogel (SGA) anode for lithium ion batteries were constructed. The SGA exhibits a three-dimensional framework interconnected with macroporous/mesoporous microstructures. Graphene aerogel could enhance the conductivity and surface area. Graphene aerogel could relieve the volume variations of SiOx during cycling. The SGA behaves excellent electrochemical performances. Abstract: Silicon monoxides (SiOx ), as a promising anode for lithium ion batteries, exhibit higher theoretical capacity than current commercial graphite, low working potential, and relatively smaller volume variations compared with pure silicon. However, the poor cycle performances, unsatisfied rate capabilities and high-cost still limit its industrial applications because of its inevitable volume variations during cycling, low conductivity and complex production process. Herein, we have constructed a SiOx /graphene aerogel (SGA) hybrid derived from low-cost rice husks, exhibiting a three-dimensional framework with macroporous/mesoporous microstructure in which SiOx nanoparticles with diameter of 40–200 nm were encapsulated. The interconnected porous aerogel microstructure could not only relieve the volume variations of SiOx during cycling and shorten the path of Li + transmission, but also improve its electrical and ion conductivity, resulting in the enhancement of electrochemical properties. As an advanced anode for LIBs, the SGA exhibits an excellent electrochemical performance in term of the specific capacity of 994.5 mAh g −1 at 200 mA g −1 after 200 cycles, and high rate capability of 937.1 mAh g −1 even at 1 A g −1 after 400 cycles. Graphic abstract: Image, graphical abstract